Genetic diversity of Panax vietnamensis var. fuscidiscus K. Komatsu, s. Zhu & S.Q. cai population in western north of vietnam detected by inter simple sequence repeat markers - Trieu, Le Ngoc; Duy, Nong Van; Chinh, Vu Tien; Tien, Tran Van (Vietnam Journal of Biotechnology, 2018)
Panax vietnamensis var. fuscidiscus is a precious medicinal plant which was recently discovered in Sin Ho and Muong Te district, Lai Chau province of Vietnam. Over exploitation of the species in the native habitat poses a serious threat to its existence. Adequate information on the nature and the extent of genetic diversity in this important species is required for developing suitable strategy for its conservation. In this study, inter simple sequence repeat markers were employed to investigate the genetic diversity and variability of 46 individuals belonging to a naturally distributed population of this variety in Vietnam. Genetic diversity at the population level was high (He = 0.2300, I = 0.3665, and PPB = 96.98 %). The group of mature individuals possessed the higher genetic diversity (HeO = 0.2291, IO = 0.3563, and PPBO = 84.34 %) as compared to group of young individuals (HeY = 0.2086, Iy = 0.3291, and PPBY = 81.5 %). The intergroup gene differentiation was high (GST = 0.0499) with the genetic distance among groups was 0.0298. The similarity coefficient among mature individuals was more moderate (Maximum = 0.873, Minimum = 0.614 and Average = 0.741) than among young individuals (Maximum = 0.916, Minimum = 0.596 and Average = 0.759). Otherwise, the number of discovered individuals was small, distribution area is narrow habitats, and the population showed the reduction in genetic diversity due to the human affects in the habitat and over-exploitation. Results on genetic diversity and variability showed that the investigated population has coped with the risk of decline and needed to be protected